2018
DOI: 10.1097/j.pain.0000000000001423
|View full text |Cite
|
Sign up to set email alerts
|

Improving pain and sleep in middle-aged and older adults: the promise of behavioral sleep interventions

Abstract: Insomnia and chronic pain are common comorbid conditions in middle-aged and older adults. Up to half of older adults with chronic pain have sleeping difficulties, which greatly increases pain-related distress and disability [46,47]. Natural age-related changes in sleep architecture and circadian rhythms further contribute to insomnia, including advanced sleep phase (falling asleep early and waking early) and reduced slow-wave sleep [33]. Unfortunately, insomnia medications can have adverse cognitive and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…A recent study conducted among 1664 older adults revealed significant racial/ethnic differences in overall sleep quality and in individual sleep components among older adults [ 93 ]. Interventional studies show that different types of therapies are effective in reducing the pain related to disability, quality of sleep, and depression in older adults with chronic pain and low back pain [ 98 , 99 ]. However, future studies are needed to understand the role of different social, psychological, physical as well as pharmacological therapy in relation to sleep disturbance and low back pain among African American older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted among 1664 older adults revealed significant racial/ethnic differences in overall sleep quality and in individual sleep components among older adults [ 93 ]. Interventional studies show that different types of therapies are effective in reducing the pain related to disability, quality of sleep, and depression in older adults with chronic pain and low back pain [ 98 , 99 ]. However, future studies are needed to understand the role of different social, psychological, physical as well as pharmacological therapy in relation to sleep disturbance and low back pain among African American older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems may impact on pain in different ways, and are part of common associated symptomatology in different pain-related conditions affecting adults and older adults, such as low back pain, headache disorders or osteoarthritis [47][48][49]. As reported in a recent review [50] several hypotheses have been made. Disrupted sleep continuity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Active pain treatment has been associated with improved sleep quality, with varying effects dependent on medications used and setting [187,188]. CBT-I is also a promising area in relation to improving chronic pain in older adults with insomnia [189].…”
Section: Pain and Disorders Associated With Painmentioning
confidence: 99%